Analisis Buku Bahasa Indonesia “Teman Baru” Siswa Kelas 1 Sekolah Dasar Berdasarkan Standar BSNP - Elvina Dwi Novitasari; Rizkya Anggun Ramadhani; Rachel Serly Delarosa; Oktavia Asmaravika Trisada; Najmuddin Karim Aqib; Panca Dewi Purwati (Pusat Riset dan Inovasi Nasional, 2025)
Language skills not only include reading and writing skills, but also listening and speaking skills that must be developed evenly since elementary school. Mastery of these four elements is very important to support good communication and achievement of competencies in various fields of study. However, not all textbooks in circulation are designed in an integrated, contextual manner, and pay attention to the developmental stages of students. The Indonesian Language Book Aku Bisa! is one of the books used in the implementation of the Merdeka Curriculum, but its feasibility needs to be assessed so that it is in accordance with the rules of effective language learning. This study aims to analyze the feasibility of the content based on the standards of the National Education Standards Agency (BSNP). The method used in this study is descriptive qualitative with a content analysis approach. The results of the study indicate that Chapter 5 has the potential to support integrated language skills, although there are some notes on the use of spelling, writing, and clarity of sentences. This study is expected to be able to provide input for the preparation of open books that are more adaptive and in accordance with the needs of elementary school students.